Collaborative distance learning system : interactive English pedagogy based on internet and e-media platform - Jahan, Tabassum Farzana; Ovee, Gholam Maruf; Rahman, Fahim Mahmudur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.